Examining Emotional Regulation's Impact on Academic Procrastination in High School Students - Firmansyah, Riky; Mariyati, Lely Ika (Indonesian Journal of Islamic Studies, 2023)
This study investigates the relationship between emotional regulation and academic procrastination among Muhammadiyah 3 Reinforcement High School students. Utilizing a correlational quantitative approach, data from 193 students in grades 11 and 12 were analyzed using SPSS 22.0. The findings indicate a significant negative correlation (rxy = -.823, p < 0.05) between emotional regulation and academic procrastination. Lower levels of emotional regulation are associated with higher procrastination tendencies, while higher emotional regulation corresponds to lower procrastination tendencies. The results underscore the importance of promoting emotional regulation skills among high school students to mitigate academic procrastination, with implications for parental involvement and school interventions. Future research should expand the sample and consider additional variables to further explore these dynamics. Highlight: Negative correlation: Emotional regulation inversely related to academic procrastination (rxy = -.823). Intervention importance: Enhancing emotional regulation crucial to reduce academic procrastination. Research expansion: Larger sample size needed, explore additional variables for comprehensive understanding. Keywoard: Emotional Regulation, Academic Procrastination, High School, Correlation, SPSS